DEVELOPMENT OF “INTRODUCTION TO NETWORKING” LEARNING MATERIALS FOR CLASS XI TKJ IN SMKN 1 KAMAL USING UNITY 3D - Mochammad Kautsar Sophan; Muchamad Arif; Yonathan Ferry Hendrawan; Indah Rodiatun Mardiyah (AIBPM Publisher, 2018)
This research is based on the condition in which printed books and modules were not enabling enough for the students to study the Introduction to Networking materials. The results were the students’ lack of learning motivation and low learning outcomes. One alternative to improve the motivation and interest in learning is using Unity 3D for learning resources. For this research, ADDIE (Analysis, Design, Development, Implementation, and Evaluation) was used as the development model. The new materials were tested to XI grade TKJ students of SMKN 1 Kamal. Results obtained from survey on small group trials were 93% and for large group trials were 90%. After they were converted to the table of achievement level and qualification, the results acquired very high qualification of 90% -100% with highly feasible description. Key Words: Learning Materials, Unity 3D, Introduction to Networking